A Comparative Study on Psychiatric Disorders: Identification of Shared Pathways and Common Agents - Kuzudisli, Cihan; Bakir-Güngör, Burcu; Bakir Gungor, Burcu (Institute of Electrical and Electronics Engineers Inc., 2022)
Distinct but closely related diseases generally present shared symptoms, which address possible overlaps among their pathogenic mechanisms. Identification of significantly impacted shared pathways and other common agents are expected to elucidate etiology of these disorders and to help design better intervention strategies. In this research effort, we studied six psychiatric disorders including schizophrenia (SCZ), anorexia (AN), bipolar disorder (BD), depressive disorder (DD), autism (AU) and attention deficit hyperactivity disorder (ADHD). Our methodology can be classified into the following two parts: In Part I, common susceptibility genes; and in Part II, genome-wide association studies (GWAS) data were used to find enriched pathways of psychiatric disorders. 59 KEGG pathways were commonly identified in both parts. 31 of these pathways are disease pathways. Pathways related to cancer and infectious diseases were predominant compared to others. Most of the acquired pathways were in accordance with previous studies in literature. A combination of susceptibility genes and GWAS data is an effective approach to identify significantly impacted pathways in multifactorial diseases. In this respect, shared modules were determined after applying hierarchical clustering of the enriched pathways. These identified modules may tell us the association of psychiatric disorders with the enriched pathways. Taken all together, common pathways and shared modules are expected to highlight the causative factors and important mechanisms behind complex psychiatric diseases, leading to effective drug discovery. © 2022 Elsevier B.V., All rights reserved.
Keywords: Functional Enrichment; Pathway Clustering; Psychiatric Disorders; Shared Pathways; Bioinformatics; Genes; Clusterings; Comparatives Studies; Functional Enrichments; Genome-Wide Association Studies; Intervention Strategy; Pathogenic Mechanisms; Pathway Clustering; Psychiatric Disorders; Shared Pathway; Susceptibility Genes; Diseases